Genomic and exoproteomic analyses of cold‐ and alkaline‐adapted bacteria reveal an abundance of secreted subtilisin‐like proteases. Issue 2 (1st February 2016) - Lylloff, Jeanette E.; Hansen, Lea B.S.; Jepsen, Morten; Sanggaard, Kristian W.; Vester, Jan K.; Enghild, Jan J.; Sørensen, Søren J.; Stougaard, Peter; Glaring, Mikkel A.
Summary: Proteases active at low temperature or high pH are used in many commercial applications, including the detergent, food and feed industries, and bacteria specifically adapted to these conditions are a potential source of novel proteases. Environments combining these two extremes are very rare, but offer the promise of proteases ideally suited to work at both high pH and low temperature. In this report, bacteria from two cold and alkaline environments, the ikaite columns in Greenland and alkaline ponds in the McMurdo Dry Valley region, Antarctica, were screened for extracellular protease activity. Two isolates, Arsukibacterium ikkense from Greenland and a related strain, Arsukibacterium sp. MJ3, from Antarctica, were further characterized with respect to protease production. Genome sequencing identified a range of potential extracellular proteases including a number of putative secreted subtilisins. An extensive liquid chromatography–tandem mass spectrometry analysis of proteins secreted by A. ikkense identified six subtilisin‐like proteases as abundant components of the exoproteome in addition to other peptidases potentially involved in complete degradation of extracellular protein. Screening of Arsukibacterium genome libraries in Escherichia coli identified two orthologous secreted subtilisins active at pH 10 and 20°C, which were also present in the A. ikkense exoproteome. Recombinant production of both proteases confirmed the observed activity.